A review of nano-composites - Mozhgan Rafizadeh; Mohammad Reza Moharreri; Kazem Khosravi; Farnaz Moshref-Javadi; Maryam Khoroushi (Isfahan University of Medical Sciences, 2012)
Introduction: Dental composite resins, as the name implies, are composite materials composed of organic and inorganic elements. The main components of dental composites are polymers, organic and inorganic filers, an initiator and an activator. In addition, some elements, referred to as silanes, are added to the surface of non-organic phases or fillers of composite resins for a stable bond between the two organic and inorganic phases. The aim of this study was to review the chemical structure of dental composites with a special emphasis on nano-composites and new composites. Review Report: This review was carried out by running a search in various databases including Pubmed and ISI Web of Science from 1987 to 2010 using the key words dental composites, nano-composite and chemical structure. Results: In the recent decade, major changes have taken place in the chemical structure of dental composites; these changes include fluoride- and calcium phosphate-releasing nano-composites and use of nano-molecular processes to construct tooth enamel by using nano-rods, nano-spheres and amelogenin. Conclusion: With a proper knowledge of changes in the chemical structure of dental composites, clinical behavior of these materials can be evaluated more properly. It appears that new changes are going to have important effects on the clinical behavior of newly introduced composites; however, further research is required in this respect. Key words: Composite resin, Nano-composites, Chemistry.